Human Anatomy : A Very Short Introduction - Klenerman, Leslie (Oxford Oxford University Press, 2015)
An understanding of the structure and function of the human body is vital for anyone studying the medical and health sciences. In this Very Short Introduction Leslie Klenerman provides a clear and accessible overview of the main systems of the human anatomy, illustrated with a number of clear explanatory diagrams.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: Human Anatomy